Activity‐dependent development of tactile and nociceptive spinal cord circuits. (26th March 2013) - Koch, Stephanie C.; Fitzgerald, Maria
Abstract : Developing brain circuits are shaped by postnatal sensory experience, but little is known about this process at the level of the spinal cord. Here we review the mechanisms by which cutaneous sensory input drives the maturation of spinal sensory circuits. Newborn animals are highly sensitive to tactile input and dorsal horn circuits are dominated by low threshold A fiber inputs. We show that this arises from the absence of the functional, targeted glycinergic inhibition of tactile activity that emerges only in the second week of life. Selective block of afferent C fibers in postnatal week 2 delays the maturation of glycinergic inhibition and maintains dorsal horn circuits in a neonatal state. We propose that in the newborn strong tactile A fiber input facilitates activity‐dependent synaptic strengthening in the dorsal horn, but that this ends with the arrival of nociceptive C fiber spinal input that drives the maturation of targeted glycinergic inhibition.